B Cell Development and T-Dependent Antibody Response Are Regulated by p38γ and p38δ - Barrio, Laura; Román-García, Sara; Díaz-Mora, Ester; Risco, Ana; Jiménez-Saiz, Rodrigo; Carrasco, Yolanda R.; Cuenda, Ana (Frontiers in Cell and Developmental Biology, 2020)
p38MAP kinase (MAPK) signal transduction pathways are important regulators of inflammation and the immune response; their involvement in immune cell development and function is still largely unknown. Here we analysed the role of the p38 MAPK isoforms p38g and p38d in B cell differentiation in bone marrow (BM) and spleen, using mice lacking p38g and p38d, or conditional knockout mice that lack both p38g and p38d specifically in the B cell compartment. We found that the B cell differentiation program in the BM was not affected in p38g/d-deficient mice. Moreover, these mice had reduced numbers of peripheral B cells as well as altered marginal zone B cell differentiation in the spleen. Expression of co-stimulatory proteins and activation markers in p38g/d-deficient B cells are diminished in response to B cell receptor (BCR) and CD40 stimulation; p38g and p38d were necessary for B cell proliferation induced by BCR and CD40 but not by TLR4 signalling. Furthermore, p38g/d-null mice produced significantly lower antibody responses to T-dependent antigens. Our results identify unreported functions for p38g and p38d in B cells and in the T-dependent humoral response; and show that the combined activity of these kinases is needed for peripheral B cell differentiation and function.